Tailoring the properties of copper nanowires by ion beam irradiation. (February 2016) - Kumar, Narinder; Kumar, Rajesh; Kumar, Sushil; Chakarvarti, S.K.
Abstract: In the present paper, we investigated the change in the properties of copper nanowires under the irradiance of 80 MeV Si 7+ ion beam. The nanowires were electrodeposited in the cylindrical pores of the track-etched polycarbonate membranes. The phase, morphology and optical absorbance of the fabricated nanowires were characterized by powder X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and UV–visible spectroscopy, respectively. The XRD study showed a face centered cubic crystal structure of copper nanowires. Further measurements with FESEM revealed that nanowires were continuous, aligned with uniform diameter having high aspect ratio. The XRD spectra of irradiated nanowires indicated an improved crystalinity at low ion fluences while it declines at higher ion fluences. The optical absorbance properties of the irradiated copper nanowires were also examined. The absorption spectra exhibited a peak at 568 nm which was attributed to the surface plasmon resonance. A significant increase in absorbance after irradiation accounts for the possibility of defects formation. The electrical properties measured from I – V characteristics showed an increase in resistivity of irradiated nanowires. Highlights: Ion irradiation-induced changes in copper nanowires have been examined. Nanowires were prepared using template method. A variation in XRD peak intensities of irradiated nanowires was observed. Ion beam irradiation caused severe damage to grain size.